CONFLICT OF AUTHORITY BETWEEN THE PRESIDENT AND THE DPR IN THE CONSTITUTIONAL CHECKS AND BALANCES MECHANISM - Fartini, Ade; Eva Hudzaefah; Amanda Roja Agustin; Ayu Safitri; Bima Guntara (AL-QISTHAS: JURNAL HUKUM DAN POLITIK, 2025)
This study explores the power dynamics between the President and the DPR in Indonesia's presidential framework, highlighting the challenges in applying the mutual oversight principle, which is often disrupted by political rivalries. Key issues include differing views on the Constitution and tensions in the lawmaking process and oversight roles. Its primary goal is to investigate the legal foundations, types of conflicts, control mechanisms, and their impacts through the case of the 2019 KPK Law revision. The method employed involves normative legal research, with a detailed analysis of constitutional documents, such as the 1945 Constitution and related rules. Findings indicate that, although the mutual oversight principle is well-regulated, its effectiveness is limited by the influence of political parties and uneven negotiations, which can lead to excessive power dominance. The main recommendation stresses the need for reforms in political culture to enhance state accountability.